Rapid detection of Burkholderia glumae causal agent of grain rot disease in rice seed from Gowa Regency, South Sulawesi using ELISA. Issue 2 (July 2021) - Darmawan, A A; Kuswinanti, T; Asman, A
Abstract: Bacterial grain rot in rice plants caused by Burkholderia glumae becomes a serious threat because it is a seed borne pathogen that causes severe damage to rice plantations in several regency at South Sulawesi. This study aimed to rapidly detect of B. glumae causal agent of grain rot disease in rice seed from Gowa Regency, South Sulawesi. Samples were obtained in 10 districts in the main rice producing areas of Gowa regency, South Sulawesi. Sampling using Non Probability Sampling method. 10 Samples that showing grain rot symptoms were detected using Indirect ELISA test with monoclonal antibody. The detection results shown that 9 out of 10 districts are confirmed positive for B. glumae bacteria.